2008
DOI: 10.1016/j.compscitech.2008.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of brazed joints of CC composite to Cu-clad-Molybdenum

Abstract: Carbon-carbon composites with either pitch+CVI matrix or resin-derived matrix were joined to copper-clad molybdenum using two active braze alloys, Cusil-ABA (1.75% Ti) and Ticusil (4.5% Ti). The brazed joints revealed good interfacial bonding, preferential precipitation of Ti at the composite/braze interface, and a tendency toward de-lamination in resin-derived C-C composite due to its low inter-laminar shear strength. Extensive braze penetration of the inter-fiber channels in the pitch+CVI C-C composites was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Recently, active brazing of ceramic-matrix and carbon-carbon composites to themselves and to high-temperature metals by Ti-containing active braze alloys has been demonstrated [8][9][10][11][12]. In previous study [13], it was found that Ti-containing Ag-Cu active metal brazes generally were sound regardless of the type of ceramic-matrix composites being joined.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, active brazing of ceramic-matrix and carbon-carbon composites to themselves and to high-temperature metals by Ti-containing active braze alloys has been demonstrated [8][9][10][11][12]. In previous study [13], it was found that Ti-containing Ag-Cu active metal brazes generally were sound regardless of the type of ceramic-matrix composites being joined.…”
Section: Introductionmentioning
confidence: 98%
“…In recent years, light weight and high‐conductivity carbon–carbon composites and graphite foams have attracted a great deal of interest and attention for thermal management applications . Graphite foams offer low density, large surface area, high ligament and bulk conductivities, and chemical and thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…However, the high density of these materials (approximately 8450–9700 kg/m 3 ) has limited their use in lightweight thermal management applications. To reduce the component weight without sacrificing the thermal conductivity and thermal expansion benefits, Cu‐clad‐Mo has been joined to graphite and, more recently, to high‐conductivity C‐C composites, silicon nitride, and ultra‐high‐temperature ZrB 2 based composites …”
Section: Introductionmentioning
confidence: 99%
“…Although active metal brazing is a simple and cost-effective technique to join ceramics and C/C has been joined to Ti [4], TiAl [5], Cu [6][7][8], and Ni [9][10][11] based alloys by active vacuum brazing. However, joining of C/C with the nickel-based single crystal super alloy has seldom been reported.…”
Section: Introductionmentioning
confidence: 99%